Various Wordings of Propaganda on Social Media: Cases from Instagram Application - Daulay, Sholihatul Hamidah; Bahar, Tanzila; Putri, Ayunda; Batubara, Putri Fadilah (Journal of Linguistics, Literacy, and Pedagogy, 2023)
A communication tool with a poor reputation in society is propaganda. This is the result of a long history of the development of propaganda and its erroneous use to influence public opinion as propaganda is used, it gets worse. In actuality, propaganda is merely a method, or depending on who uses it and the objectives it seeks, a communication tool may be helpful or terrible to succeed. People's lives have been impacted by the advancement of communication technologies. New media, which eventually gave rise to social media, is one area of communication technology development. since thing. The mass media currently holds a very critical position in terms of providing access to individuals who require information. The existence of the mass media is thought to be able to aid humans by facilitating access for people to obtain the information they require, in accordance with human nature, specifically, curiosity about everything. Cangara (2002) asserts that social media is a tool employed in transmitting messages from the source to the audience.